Improving the quality of experience in terms of SINR by modelling a millimetre wave pico-cellular network: a potential (5G) cellular network with a pico-cell technology deployment at 28 GHz operating frequency. (2015) - Zoubi, Zaid M.; Vial, Peter James; Premaratne, Prashan; Alshbatat, Abdel Ilah Nour
Fifth generation technology (5G) is causing researchers to find ways to maximise the mobile telecommunication network capacity. This term has led to the discovery that there is a vast spectrum in the millimetre wave (mmWave) band between 3 GHz and 300 GHz which can be used to deploy small-cell technology over a highly populated service area. This paper proposes a 5G cellular system with a multi-pico cell deployment at 28 GHz operating frequency in order to reduce the signal-to-interference-noise ratio and thus improve the quality of user experience (QoE). Our study also provides a comparison between the suggested mmWave model and the cellular Fourth Generation/Long Term Evolution (4G/LTE) at 1900 MHz. We established and tested both systems over a 1.2 km² service area. Finally, we investigated that our proposed system enabled a cell throughput three times the maximum cell throughput of 4G/LTE1900.